Architectural Design and Microstructural Engineering of Metal–Organic Framework‐Derived Nanomaterials for Electromagnetic Wave Absorption. Issue 1 (9th November 2022) - Xu, Xueqing; Li, Deshun; Li, Li; Yang, Zhiwang; Lei, Ziqiang; Xu, Yuxi
Abstract : Metal–organic frameworks (MOFs) derivatives are developing family of functional materials for electromagnetic wave (EMW) absorption. Their tailored structures, controllable compositions, high porosity, and versatile functions offer immense advantages for the construction of excellent EMW absorption materials. Nevertheless, it is crucial and challenging to understand the unique role of rationally designing art and tailoring the microstructures of MOF‐derived materials for EMW absorption. In this review, advances in rational architectural design strategy and the elaborate control of microstructures are outlined to promote the EMW absorption performance of MOF‐derived materials. In addition, the derived key information regarding the superiority and composition–structure–performance relationships of the engineered MOF‐derived materials with advanced components and nanostructures is comprehensively summarized. Finally, the insight into the challenges of future development in MOF‐derived EMW absorption materials is presented. Abstract : This review introduces the current trends in metal–organic framework (MOF)‐derived electromagnetic wave (EMW) absorption materials in detail. Rationally designed architectures and cropped microstructures for boosting the EMW absorption performance are discussed. The composition–structure–performance relationships of engineered MOF‐derived materials are summarized. Future challenges and design strategies for MOF‐derived EMW absorber materials are provided.